Microbial mediated remediation of heavy metals toxicity: mechanisms and future prospects - Tang, Haiying; Xiang, Guohong; Xiao, Wen; Yang, Zeliang; Zhao, Baoyi (Frontiers in Plant Science, 2024)
Heavy metal pollution has become a serious concern across the globe due to their persistent nature, higher toxicity, and recalcitrance. These toxic metals threaten ed the stability of the environment and the health of all living beings. Heavy metals also enter the human food chain by eating the contaminated foods and cause toxic effects on human health. Thus, remediation of HMs polluted soils is mandatory and it needs to be addressed at higher priority. The use of microbes is considered as a promising approach to combat the adverse impacts of HMs. Microbes aided in the restoration of deteriorated environments to their natural condition, with long-term environmental effects. Microbial remediation prevents the leaching and mobilization of HMs and they also makes the extraction of HMs simple.Therefore, in this context recent technological advancement allowed to use of bioremediation as an imperative approach to remediate polluted soils. Microbes use different mechanisms including biosorption, bioaccumulation, bioleaching, bio-transformation, bio-volatilization and bio-mineralization to mitigate toxic the effects of HMs. Thus, keeping in the view of toxic HMs here in this review we exploredexplores the role of bacteria, al, fungi and algae in for bioremediation of polluted soils. We alsoThis review also discusses the summarized various approaches that can be used to improve the efficiency of microbes to remediate HMs polluted soils. Finally, we It also highlight highlighted many different research gaps that must be can be solved in future study programs to improve bioremediation results.efficency.